Influences on the trajectory and subsequent outcomes in CDKL5 deficiency disorder. Issue 2 (27th November 2021) - Leonard, Helen; Junaid, Mohammed; Wong, Kingsley; Aimetti, Alex A.; Pestana Knight, Elia; Downs, Jenny
Abstract: Objective: The study investigated the effect of seizure and medication burden at initial contact with the International CDKL5 Disorder Database on subsequent development and clinical severity and compared quality of life among those whose development progressed, remained stable, or regressed between baseline and follow‐up. Methods: The effects of seizure and medication burden at baseline (high or low) on the CDKL5 Disorder Severity Scores and CDKL5 Developmental Score (CDS) at follow‐up were assessed using linear and negative binomial regressions, respectively, with adjustment for age at baseline, gender, and follow‐up duration with and without genotype. Seizure and medication burden were defined by average daily seizure count (high, ≥5/day; low, <5/day) and number of antiseizure medications (high, ≥3/day; low, <3/day), respectively. The effects of change in CDS over time (improved, stable, or deteriorated) on Quality of Life Inventory–Disability (QI‐Disability) total and domain scores at follow‐up were assessed in those aged at least 3 years at follow‐up using linear regression models with adjustment for baseline CDS, gender, and follow‐up duration. Results: The expected follow‐up CDS was lower for individuals with high compared to low seizure burden at baseline (β = −.49, 95% confidence interval [CI] = −.84 to −.13). The average total QI‐Disability score was 5.6 (95% CI = −.2 to 11.5) points higher among those with improved compared with stable or deteriorating CDS and 8.5 (95% CI = 3.1–13.8) points lower for those with deteriorating compared to stable or improved CDS. Significance: Our finding that later development showed slight improvement in those with better earlier seizure control even after adjustment for genotype suggests that the trajectory for an individual child is not necessarily predetermined and could possibly be influenced by optimal seizure management. This has implications for children's quality of life.